THE EFFECT OF COMPANY SIZE, RETURN ON ASSETS , SOLVENCY, AND OPINION AUDITING TO AUDITING DELAY ON COMPANY CONSUMER GOOD YANG REGISTERED IN EXCHANGE EFFECT INDONESIA (Jurnal Ipteks Terapan, 2023)
This research was conducted to test the effect of company size, Return on assets (ROA), solvency, and audit opinion on audit delays in companies consumer goods listed on the Indonesian Stock Exchange in 2019-2021 is good partially or simultaneously. From a total population of 55 companies and Based on the specified criteria, 20 sample companies were obtained for the last 3 years. This research is quantitative research, the data is processed in the form of secondary data which is measured using a ratio scale in processing statistics. Technique analysis Which used it is regression linear multiple. Based on the results of analysis using the t test (partial) and F test (simultaneous) show that Size company, ROA, Solvency, And Opinion Auditing influential negative And No significant to auditing delay